Rediscovery of Termitoloemus Marshalli Baranov (diptera: Calliphoridae: Bengaliinae), A Predator of Termites, after 78 Years - Singh, Sudhir (Indian Forester, 2014)
Termitoloemus marshalli Baranov (Diptera: Calliphoridae: Bengaliinae) was known to the science only through one male holotype and two female paratypes collected from Kanpur (Uttar Pradesh, INDIA) in 1935. Since then no specimen was ever captured or identified by any worker. In the present paper its rediscovery after 78 years is reported. It was found predating voraciously on the workers and soldiers of the termites Odontotermes obesus and O. giriensis in Assam and in Dehradun. Material identified is deposited in National Insect Reference Collection, FRI, Dehradun and shall also be deposited with other national and international insect depositories so that the species may be well understoodand exploited for termite biological control initiatives.